Peri-implant maintenance of immediate function implants: a pilot study comparing hyaluronic acid and chlorhexidine - M de Arau´ jo Nobre (Journal compilation 2007 Blackwell Munksgaard, 2007)
In implants, maintenance assumes an important role. The role of chlorhexidine (CHX) is well known in maintenance, while only limited evidence exists on the practical use of hyaluronic acid (HA).